Classroom Interaction Patterns of English Teacher Candidates in Micro Teaching - Telaumbanua, Yasminar Amaerita; Berlin Sibarani; Masitowarni Siregar (PT Inovasi Pratama Internasional, 2022)
The research objective was to describe what and how classroom interaction patterns and what factors influenced English teacher candidates in micro-teaching. The research problem was what and how classroom interaction patterns and what factors they make in the performance of the basic skill. The research method used was qualitative research. The researchers used videotape and in-depth interviews as the research instruments to collect the data needed. The total respondents were 66 students as English teacher candidates. The results and important findings from the videos were obtained that the English teacher candidates had good, good enough, enough, and bad classroom interaction patterns. In group work, the interaction between student and student was bad. A similar thing happened in closed-ended teacher questioning, the interaction between student-teacher-student was bad too meanwhile in open-ended teacher questioning was good enough. In the choral response, the interaction pattern between student-content was good. The last was teacher talks, the interaction pattern of student-teacher was enough. Some factors influenced classroom interaction patterns such as the result from the in-depth interview that were the linguistic ability level of English teacher candidates, ability to select interesting topics, ability to master the content, ability to manage the classroom, and lack of confidence. In a conclusion, classroom interaction patterns were at different levels influenced by some factors, monotonous and mostly similar patterns for all the English teacher candidates as happened in a conventional classroom.